Criteria for the admissibility of digital (electronic) evidence in criminal proceedings - V. V. Romaniuk; S. Ye. Ablamskyi (Law and Safety)
The article is devoted to consideration of modern problems of determining the admissibility of digital (electronic) evidence in criminal proceedings. Given the importance of the outlined issues, the main purpose of the study is to characterize each component of the admissibility of such evidence, namely: the proper source of receipt, the proper subject, and the proper method of collection. It is emphasized that the biggest doctrinal problem that creates an obstacle in the definition of such criteria is the lack of a unified scientific vision regarding the concept of digital (electronic) evidence and the definition of its source. The existence of three scientific approaches to the solution of this problem was established, taking into account the author's position on possible ways of its elimination. Some practical aspects related to the problems of compliance with the criteria of admissibility of digital (electronic) evidence during the investigation of criminal offenses are disclosed.